Get started with Minecraft - Moltz, John (Peachpit Press, 2014)
"Minecraft comes with no real instructions, so surviving your first days in Minecraft can be full of frustrations, once you get the game installed. Don't worry. In this downloadable video, we'll explain how to get and install the game and survive your first day. You'll also see how to expand the game and play with friends."--Resource description page.